Housing Disputes and Politics; Socio-Political Context of the Tenant-Protection Schemes in Southeast and East-Central Europe, 1918–1928 - Aleksandar R. Miletić (Токови историје, 2016)
This comparative study analyses a specific socio-political context of the processes that came with the implementation of a housing rent control system in Bulgaria, Yugoslavia, Czechoslovakia and Poland during the first interwar decade. It studies specific interactions between mainstream politics and landlords’ and tenants’ interest associations. The paper deals with the evolution of the attitudes of tenants’ and landlords’ associations towards the politics and their active participation therein.